Acute and Subacute Toxicity Assessment of Lutein in Lutein‐Deficient Mice. Issue 10 (11th September 2013) - Nidhi, Bhatiwada; Baskaran, Vallikannan
Abstract Dietary lutein consumption is lower than the actual recommended allowances to prevent macular degeneration; thus dietary lutein supplements have been recommended. This study aimed to investigate potential adverse effect of lutein from Tagetes erecta in lutein‐deficient (LD) male mice. Preliminary acute toxicity study revealed that the LD50 exceeded the highest dose of 10000 mg/kg BW. In a subacute study, male mice were gavaged with 0, 100, 1000 mg/kg BW/day for a period of 4 wk. Plasma lutein levels increased dose dependently (P < 0.01) after acute and subacute feeding of lutein in LD mice. Compared to the control (peanut oil without lutein) group, no treatment‐related toxicologically significant effects of lutein were prominent in clinical observation, ophthalmic examinations, body, and organ weights. Further, no toxicologically significant findings were eminent in hematological, histopathological, and other clinical chemistry parameters. In the oral subacute toxicity study, the no‐observed‐adverse‐effect level (NOAEL) for lutein in LD mice was determined as 1000 mg/kg/day, the highest dose tested.